Legal perspectives on sustainability / edited by Margherita Pieraccini and Tonia Novitz. - Pieraccini, Margherita; Novitz, Tonia (Bristol University Press, 2020)
This important volume steps beyond conventional legal approaches to sustainability to provide fresh insights into perhaps one of the most critical global challenges of our time. Offering analysis of sustainability at land and sea alongside trade, labour and corporate governance perspectives, this book articulates important debates about the role of law. From impacts on local societies to domestic sustainable development policies and major international goals, it considers multiple jurisdictional levels.With original, interdisciplinary research from experts in their legal fields, this is a rounded assessment of the complex interplay of law and sustainability - both as it is now and as it should be in the future.